Strategi Pemasaran Daya Tarik Taman Wisata Iman Sitinjo Kabupaten Dairi Sumatera Utara - Sinaga, Elizabeth M R; Suryasih, Ida Ayu; Ariwangsa, I Made Bayu (JURNAL DESTINASI PARIWISATA; Vol 11 No 1 (2023): VOL 11, NO 1 (2023): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2023.v11.i01.p22, 2023)
The attraction of Taman Wisata Iman Sitinjo is one of the attractions that is currently pursuing marketing activities. The lack of promotional media as a means of marketing products and the lack of market from among tourists make the attraction of Taman Wisata Iman Sitinjo less well known by the wider community. The importance of marketing strategy is as a means of introducing, communicating, and marketing the attractiveness value of Taman Wisata Iman Sitinjo to be directed and effective. Therefore, this research is important to be carried out and aims to determine the internal and external factors of Taman Wisata Iman Sitinjo, so that the right marketing strategy can be known for the attractiveness of Taman Wisata Iman Sitinjo. The research method used in this study is qualitative. Data was collected through observation, interviews and documentation. The resulting marketing strategy is the result of a SWOT analysis obtained from the identification of attractiveness conditions that result in the SO strategy, namely creating an image of the attractiveness of Taman Wisata Iman Sitinjo as a quality attraction and maintaining and improving the quality of attraction to be able to attract visitors to make a return visit. ST's strategy is to create innovations that attract more tourists and create a brand image to create tourist confidence in the attractiveness of Taman Wisata Iman Sitinjo. The WO strategy is to improve the quality of tourism human resources and improve the quality and service facilities for tourists. The last strategy is WT strategy, namely increasing the promotion of the attractiveness of Taman Wisata Iman Sitinjo through social media as well as the construction and provision of tourism supporting facilities. Keywords: tourism marketing strategy, tourist attraction, Taman Wisata Iman Sitinjo